Social role of the income tax in Ukraine - Yeltsova, Y. Y. (My University, 2020)
Taxes are one of the important sources of budget replenishment and an instrument of state regulation of socio-economic relations. In the current. Taxes are one of the important sources of budget replenishment and an instrument of state regulation of socio-economic relations. In the current tax system of Ukraine, one of the central places among all taxes is the personal income tax, which is a major lever for regulating the distribution between the state and the population of financial resources. This tax is one of the most stable and effective sources of budget revenue generation, but it directly influences the level of income and distribution of the population, thus acting as a social regulator. of Ukraine, one of the central places among all taxes is the personal income tax, which is a major lever for regulating the distribution between the state and the population of financial resources. This tax is one of the most stable and effective sources of budget revenue generation, but it directly influences the level of income and distribution of the population, thus acting as a social regulator.
Keywords: tax system; taxes